Pesquisa de satisfação com acadêmicos do curso de tecnologia em logística em relação aos professores e infraestrutura do campos - Lima, Kelly Cristina dos Santos (Universidade Federal do Tocantins, 2020)
Achieving satisfaction survey is of great importance for the enrichment and further development of quality education in universities, whether private or public. Knowledge of the academic expectations for their educational institution is essential to building a solid higher education and also to direct the course of collegiate efforts in one focus. Thus, this paper tried to measure the level of satisfaction of the academic course of Technology in Logistics Federal University of Tocantins with regard to the judgment of scholars without regard to the quality of teaching, assessment course curriculum composition, knowledge technical attendance and ethical values of teachers, identifying the appropriateness of curriculum content, practices and teaching resources of teachers having equivalence between disciplines and the demands of the labor market. In other words, seeks to analyze elements linked to satisfaction of the students as: institutional organization, faculty and infrastructure physical. How much the nature of the research, this work resorted to field research and literature. With regard to the shape, you may consider quality and quantity. As for the results of this study demonstrated that academics evaluate positively the IES and are satisfied with the way it is approached and passed the contents in class, and demonstrate satisfaction also in relation to infrastructure.